Sisters red - Pearce, Jackson, 1984- (Little, Brown, 2010)
After a Fenris, or werewolf, killed their grandmother and almost killed them, sisters Scarlett and Rosie March devote themselves to hunting and killing the beasts that prey on teenaged girls, learning how to lure them with red cloaks and occasionally using the help of their old friend, Silas, the woodsman's son.